Peripheral Blood‐Derived Endothelial Progenitor Cells Enhance Vertical Bone Formation. (30th April 2013) - Zigdon‐Giladi, Hadar; Bick, Tova; Morgan, Elise F.; Lewinson, Dina; Machtei, Eli E.
Abstract Background This study presents a novel cell‐based approach for extra‐cortical bone regeneration. Objective To enhance vertical bone formation by combining guided bone regeneration and transplantation of peripheral blood‐derived endothelial progenitor cells (EPCs) in a rat calvaria model. Materials and Methods EPCs were isolated from peripheral blood of inbred rats. Gold domes (7 mm radius, 5 mm height) were filled with β‐tricalcium phosphate (βTCP) mixed with 5 × 105 EPC. Domes filled with βTCP served as control (CNT). Rats were sacrificed after 3 months. Vertical bone augmentation was analyzed using histology, histomorphometry, and microcomputed tomography (μCT). Results In all rats, hard tissue filled the space under the dome. Histomorphometric analysis revealed that EPC transplantations doubled vertical bone height (EPC 4.04 ± 0.22 mm vs CNT 2.29 ± 0.22 mm, p ≤ .001). EPC also caused ∼50% increase in bone area fraction (EPC 47.3 ± 3.1% vs CNT 31.1 ± 2.7%, p ≤ .003). μCT results also showed that bone volume fraction (BV/TV) was higher in EPC group (p = .0169). In both groups, BV/TV declined from the bottom to the top of the samples. No differences in tissue mineral density were found between EPC and CNT groups. Conclusion EPC transplantation significantly improved bone formation especially in the areas that are remote from the original bone.